Appraisal of the PIBD-classes Criteria: A Multicentre Validation. (26th May 2020) - Ledder, Oren; Sonnino, Micol; Birimberg-Schwartz, Liron; Escher, Johanna C; Russell, Richard K; Orlanski-Meyer, Esther; Matar, Manar; Assa, Amit; Tzion, Raffi Lev; Shteyer, Eyal; Griffiths, Anne; Turner, Dan
Abstract: Introduction: The PIBD-classes criteria were developed to standardise the classification of children with inflammatory bowel disease [IBD], from Crohn's disease [CD], through IBD-unclassified [IBD-U], to typical ulcerative colitis [UC]. We aimed to further validate the criteria and to explore possible modifications. Methods: This was a multicentre retrospective cohort study of children diagnosed with IBD with at least 1 year of follow-up. Clinical, radiological, endoscopic, and histological data were recorded at diagnosis and latest follow-up, as well as the 23 items of the PIBD-classes criteria. The PIBD-classes criteria were assessed for redundant items, and a simplified algorithm was proposed and validated on the original derivation cohort from which the PIBD-classes algorithm was derived. Results: Of the 184 included children [age at diagnosis 13 ± 3 years, 55% males], 122 [66%] were diagnosed by the physician with CD, 17 [9%] with IBD-U, and 45 [25%] with UC. There was high agreement between physician-assigned and PIBD-classes generated diagnosis for CD [93%; eight patients moved to IBD-U] and for UC [84%; six moved to IBD-U and one to CD]. A simplified version of the algorithm with only 19 items is suggested, with comparable performance to the original algorithm [81% sensitivity and 81% specificity vs 78% and 83% for UC; and 79% and 95% vs 80% and 95% for CD, respectively]. Conclusions: The PIBD-classes algorithm is a useful tool to facilitate standardised objective classification of IBD subtypes in children. A modified version of the PIBD-classes maintains accuracy of classification with a simplified algorithm.